Localization of Staphylococcus aureus in Infected Airways of Patients with Cystic Fibrosis and in a Cell Culture Model of S. aureus Adherence - Ulrich, Martina; Herbert, Silvia; Berger, Jurgen; Bellon, Gabriel; Louis, Dominique; Munker, Gerd; Doring, Gerd (American journal of respiratory cell and molecular biology, 1998)
Staphylococcus aureus causes chronic respiratory tract infections in patients with cystic fibrosis (CF). Using immunofluorescence and scanning and transmission electron microscopy we located S. aureus in lung specimens of three infected CF patients, in a nasal polyp of one CF patient, and in a suspension cell culture system of primary nasal epithelial cells in vitro. Very little of S. aureus was attached to the lung epithelium, whereas abundant S. aureus was detectable in the mucus of obstructed airways. Similarly, S. aureus adhered to components of secreted mucus on primary nasal epithelial cells of CF patients and healthy control subjects, grown as cell balls in vitro (bacteria/cell +/- SD: CF: 21.9 +/- 1.5; controls: 22. 0 +/- 5.8). Mucus depletion of cell balls prior to incubation with S. aureus resulted in a significantly reduced binding (bacteria/cell +/- SD: CF: 4.2 +/- 0.3; P < 0.001; controls: 5.0 +/- 1.3; P < 0. 007). Binding of S. aureus to cell balls from CF patients or control subjects did not differ significantly. When cell balls were treated with human neutrophil elastase, hypersecretion caused removal of S. aureus from cell-associated mucus. The results suggest that S. aureus adheres primarily to mucus components of the respiratory epithelium and that significant differences do not exist in binding of S. aureus to CF or non-CF cells.